Food for thought. Rainforest carrion-feeding butterflies are more sensitive indicators of disturbance history than fruit feeders. (January 2018) - Whitworth, Andrew; Pillco Huarcaya, Ruthmery; Gonzalez Mercado, Harryson; Braunholtz, Laura Dominie; MacLeod, Ross
Abstract: Tropical forests have, and in many areas continue to experience both severe and subtle forms of human disturbance; most commonly from hunting, logging and clearance for agriculture. The ability to detect a full range of impacts is essential to understanding how biodiversity responds to human disturbance. Since monitoring the entire biodiversity of a tropical forest is an impossible task, specific groups of biodiversity are often used as biological indicators. Due to their relative ease in detection and identification, their sensitivity to environmental change and their short generation time, butterflies are suggested to be one of the most effective biodiversity indicators for tropical forest monitoring. However, most biodiversity monitoring of tropical ecosystems using butterflies relies only on one sub-group, the fruit-feeding butterflies, or Nymphalidae. Here we assess for the first time if the use of carrion-feeding butterfly communities might improve our ability to detect and monitor human impacts and conservation management outcomes in tropical forests. We analysed species richness, abundance and community composition of rainforest fruit and carrion butterfly communities to see how effectively they detect known differences in forest disturbance history, between three different vertical strata of rainforest, and assess whether they provide stable results across different seasons. We found that compared to fruit-feeding butterflies, sampling carrion-feeders detected greater species richness and abundance for the same survey effort, detected more pronounced effects of known differences in historic disturbance, and showed greater temporal stability in biodiversity patterns across the year. We also identify for the first time a series of indicator butterfly species and tribes that could be used as biological indicators to study biodiversity responses to human disturbance and differences across vertical strata of the rainforest. We therefore suggest that carrion-feeding butterfly communities will be a powerful addition to the family of indicators groups that are available for monitoring the impacts of human disturbance on tropical biodiversity.